On the possible reason for superconductivity strengthening in multiwall carbon nanotubes - Gaididei, Yu.B.; Loktev, V.M. (Физика низких температур, 2006)
Basing on the structural peculiarity of two-layer graphene which consists of translational
and energetical nonequivalency of carbon atoms from different sublattices, it is shown that the
density of long-wave electronic states at the Fermi level is finite (in contrast to the monolayer
graphene). It is suggested that the same may be the reason why the critical temperature of
superconducting transition in multiwall nanotubes more than ten times higher than in single-wall
nanotubes.